PEMANFAATAN AIR UNTUK KEPENTINGAN BISNIS (STUDI PUTUSAN NOMOR 91/PID.B/LH/2021/PN TTE): Water Utilization for Business Purposes (Study of Decision Number 91/Pid.B/LH/2021/PN Tte) - Dinda Nabila Ramadhanty Lazuardi; Sri Untari Indah Artati (AMICUS CURIAE, 2025)
Utilization of groundwater for business purposes must have a permit, this is stated in Law Number 17 of 2019 related to Water Resources (UU SDA). Identification problems raised are what the legal consequences are for individuals who do not have a water utilization permit for business purposes and how sanctions can be applied to individuals who have utilized water for business purposes without a permit. To answer the problem, the normative juridical method is used, which is descriptive, using secondary data that is analyzed qualitatively and deductively concludes. By the findings result and conclusion of the analysis of Court Decision Number 91/Pid.B/LH/2021/PN Tte with Law Number 17 of 2019 related to Water Resources (UU SDA), the results obtained are that Iqbal Barady was found guilty of using groundwater without using a water utilization permit and selling the groundwater to residents. Iqbal Farady was sentenced to imprisonment by Law Number 17 of 2019 related to Water Resources (UU SDA).